Communion, Diversity and Salvation : the Contribution of Jean-Marie Tillard to Systematic Ecclesiology. - Flanagan, Brian (Ecclesiological investigations., 2011)
The use of the term communion is a significant component of much contemporary ecclesiology, but its prominence calls attention to wider questions regarding ecclesiological method. Brian Flanagan addresses the questions of how to charancterize a systematic ecclesiology and the possibility of a systematic communion ecclesiology by investigating the concept of communion in the work of Jean-Marie Tillard, OP. Tillard's theology is notable as the most prominent Roman catholic communion ecclesiology. Flanagan argues, that Tillard contributes to systematic ecclesiology by defining the concept of comm.